PENGARUH KOMPENSASI, DISIPLIN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN TOKO ABC KARANGANYAR - Giyono Giyono (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2019)
Compensation, discipline to the work and work motivation are important factors in efforts to develop human resources in improving employee performance. This study aims to dig the influences of compensation, discipline to the work and work motivation of job performance. The data used in this study is primary data from questionaires. Respondents in this study were 45 persons who are employees of ABC store Karanganyar. The validity and reliability, linear regression, determination, and hypothesis tested by SPSS version 16.0 programme. The results showed from partially and simultaneous hypothesis testing, the variables of compensation, discipline to the work and work motivation effect on employee performance.Keywords: compensation, discipline to the work, work motivation, perfomance